Silicon diimide gel as an efficient stationary phase in thin layer chromatography for acid-sensitive organic compounds. Issue 80 (26th September 2017) - Kitney, Stuart P.; Sajedin, Seyed M.; Rocher, Vincent; Cheng, Fei; Kelly, Stephen M.
Abstract : Mesoporous silicon diimide gel (Si(NH)2 ) n is a suitable, efficient, and stable stationary phase for thin layer chromatography, that has the capacity to separate organic compounds chromatographically without decomposing acid-sensitive functions or bonds. Abstract : We report the use of mesoporous silicon diimide gel as a basic stationary phase in thin layer chromatography for the characterisation and purification of acid-sensitive compounds. The gel is prepared by a simple sol–gel process and exhibits a large specific surface area, almost monodisperse pores and basic properties due to free-hanging amine groups.